Next-generation free-electron radiation X-ray source using a 2D materials platform - Liu, Yutai (Nanyang Technological University, 2023)
In the quest for a more convenient and cost-effective X-ray source, traditional methods like X-ray tubes and synchrotrons face limitations. X-ray tubes, though portable, emit X-rays determined by their fixed materials. On the other hand, synchrotrons are expensive and time-consuming to access. Researchers employed the model of a tunable table-top X-ray generator that makes use of free-electron radiation and 2D materials to overcome these difficulties. However, it should be noted that there is a lack of literature review concerning the compilation of van der Waals materials, and this particular model is a recent inclusion. By modeling 10 typical vdW materials, our article closes this gap and may serve as a useful resource for future researchers in related domains. This study offers insights into the strengths and limitations of diverse materials, paving the way for future research in the platform materials of compact and high-quality X-ray sources.